Common Microbes and Antibiotic Resistance in Ocular Infections at an Urban Public Tertiary Care Hospital. (17th February 2022) - Geevarghese, Alexi; Shah, Payal; Lopez, Jennifer; Tsui, Edmund; Raju, Leela
ABSTRACT: Purpose: We aim to describe ocular infection epidemiology for a public tertiary care hospital in New York City (NYC). Methods: We retrospectively reviewed 558 patients with ocular isolates from conjunctival, corneal, and intraocular culture from 2009 to 2017 for microbial growth and antimicrobial sensitivities. Results: In total, 185 ocular cultures (33%) had growth and the most commonly isolated microbes overall were Staphylococcus aureus (S. aureus) (23%), coagulase-negative Staphylococcus (CoNS) (23%), Pseudomonas aeruginos a (P. aeruginosa) (16%), and Streptococcus viridans (S. viridans) group (11%). The most common microbes within corneal (n = 61), conjunctival (n = 34), and intraocular isolates (n = 9) were P. aeruginosa (37.7%), S. aureus (35.3%), and S. viridans group (33.3%), respectively. Proportion of isolates exhibiting multi-drug resistance decreased over time ( P = .006). Conclusions: The microbial epidemiology of ocular infection of a public NYC hospital was distinct from other geographic locations, underscoring the importance of examining local profiles to more precisely inform empiric therapy.